Photodegradation of Rhodamine B over Biomass-Derived Activated Carbon Supported CdS Nanomaterials under Visible Irradiation - Huang, Hai-Bo; Wang, Yu; Cai, Feng-Ying; Jiao, Wen-Bin; Zhang, Ning; Liu, Cheng; Cao, Hai-Lei; Lü, Jian (Frontiers in Chemistry, 2017)
A family of new CdS@SAC composite materials was successfully prepared through the deposition of as-synthesized CdS nanomaterials on various lotus-seedpod-derived activated carbon (SAC) materials. The SAC supports derived at different activation temperatures exhibited considerably large surface areas and various microstructures that were responsible for the enhanced photocatalytic performance of CdS@SAC composite materials towards the photodegradation of rhodamine B (RhB) under visible irradiation. The best-performing CdS@SAC-800 showed excellent photocatalytic activity with a rate constant of ca. 2.40×10–2 min–1, which was approximately 13 times higher than that of the CdS precursor. Moreover, the estimated band gap energy of CdS@SAC-800 (1.99 eV) was significantly lower than that of the CdS precursor (2.22 eV), which suggested considerable strength of interface contact between the CdS and carbon support, as well as efficient light harvesting capacity of the composite material. Further photocatalytic study indicated that the SAC supports enhanced synergistically the accessibility of organic substrates, the efficiency of solar energy harvesting, as well as the separation of photogenerated electrons and holes in this system. Improved photocatalytic activity of the composite materials was largely due to the increased generation of active species such as h+, OH•, O2•− etc. This work provides a facile and low-cost pathway to fabricate composite photocatalysts for viable degradation of organic pollutants.